2014
DOI: 10.1002/pi.4737
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic assembly of uniform fluorescent microbeads from quantum‐dot‐loaded fluorine‐containing microemulsion

Abstract: The assembly of a fluorine‐containing microemulsion of poly[(2‐(N‐ethylperfluorobutanesulfonamido)ethyl acrylate)‐co‐(methyl methacrylate)‐co‐(butyl acrylate)‐co‐(glycidyl methacrylate)] and N‐acetyl‐l‐cysteine‐capped CdTe quantum dots via a microfluidic technique afforded uniform microbeads with adjustable sizes and good fluorescence properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These dried supracolloidal fibers could be transferred to light-weight highly porous nanocomposite materials. In addition, fluorescent quantum dot (QD)-loaded microbeads were fabricated in microfluidic devices by Chen et al [57], based on functional fluorine-containing microemulsions with copolymers as the core and glycidyl methacrylate (GMA) as the shell.…”
Section: Multi-emulsion Of Microdropletsmentioning
confidence: 99%
“…These dried supracolloidal fibers could be transferred to light-weight highly porous nanocomposite materials. In addition, fluorescent quantum dot (QD)-loaded microbeads were fabricated in microfluidic devices by Chen et al [57], based on functional fluorine-containing microemulsions with copolymers as the core and glycidyl methacrylate (GMA) as the shell.…”
Section: Multi-emulsion Of Microdropletsmentioning
confidence: 99%
“…The methodology has been implemented for more high-capacity and monodisperse particle production using a flow-focusing nozzle to form chloroform droplets of QDs and poly­(styrene-co-maleic anhydride) dispersed in a reactor volume filled with an aqueous phase (concentration-controlled flow focusing, CCFF). ,, In an adaption of the CCFF technique, the QD/poly­(styrene-co-maleic anhydride) polymer/solvent mixture is emulsified into an aqueous phase by passing the mixture through a (Shirasu) porous glass membrane (SPG-CCFF) to form monodisperse droplets with a smaller lower bound (∼1 μm) for the microbead size range than can be achieved through CCFF. Flow focusing and solvent extraction in microfluidic geometries has also been used to form either poly­(lactide- co -glycolide)/QD or polycaprolactone/QD , QD/polymer composites or composites of nanoparticles coated with QDs …”
Section: Introductionmentioning
confidence: 99%
“…Flow focusing and solvent extraction in microfluidic geometries has also been used to form either poly(lactide-co-glycolide)/QD 103 or polycaprolactone/ QD 104,105 QD/polymer composites or composites of nanoparticles coated with QDs. 106 From the above review, preparation methods in which the QDs are embedded within polymer microbeads during bead formation (solvent extraction and copolymerization) have the most advantages, as predefined labels can easily be incorporated, the QDs extend throughout the microbead interior, allowing a more easily read label, and these methods combine both barcoding and microbead formation in one step. However, the studies using these methods have also shown that the incorporation of the QDs into the polymer matrix can result in aggregation of the QDs in the polymer microbead composite.…”
Section: ■ Introductionmentioning
confidence: 99%